PENGARUH PROFESSIONAL IDENTITY TERHADAP TURONVER INTENTION YANG DIMEDIASI OLEH EMPLOYEE ENGAGEMENT DAN JOB SATISFACTION PADA KARYAWAN PT. TELKOM INDONESIA DI KOTA BANDA ACEH - Raka Bagus Kusasti; Muliati Usman (Departemen Manajemen, 2022)
This study shows that Job Satisfaction and Employee Engagement are related to Professional Identity and Turnover Intention to Employees of PT. Telkom Indonesia in Banda Aceh City. Therefore, this study provides literature on the contribution to professional identity and turnover intention through the mediating role of job satisfaction and employee. This study uses COR theory which shows that when employees have professional identity, employee engagement, job satisfaction, they will feel they have many valuable resources. The sampling technique used is probability sampling with the type of sampling selected is stratified random sampling. This study uses Hierarchical Linear Modeling (HLM) as an analytical method to determine the effect of the variables involved. Based on the results of HLM that Professional Identity has a negative effect on Turnover Intention, while Employee Engagement and Job Satisfaction have a negative effect on Turnover Intention. In addition, Professional Identity has a positive effect on Employee Engagement and Job Satisfaction. In this relationship, Employee Engagement and Job Satisfaction have an effect as a mediating relationship between Professional Identity and Turnover Intention.